Echanges et transformations de l’Annonciation : D’un groupe statuaire en marbre (Toulouse, Musée des Augustins,XIIe siècle) à un bas-relief en bronze d’Igor Mitoraj (Rome, Santa Maria degli Angeli, 2006) - Sandra Gorgievski (Anglophonia)
The biblical episode of the Annunciation provides a fascinating iconographic motif lending itself to a close examination of artistic and religious frameworks, both in medieval Christendom and nowadays. In spite of the underlying paradox that the mystery of the Incarnation of Christ cannot be represented, cult objects like statues offer a valuable contribution to the history of this emblematic scene. In spite of radically distinct cultural models and divergent religious practice, both the vivid statues from a lost XIIth century Romanesque church in Toulouse and the 2006 newly sculpted doors of a church in Rome attempt to stage the message sent by God through the Angel Gabriel. In the modern sculpture, obvious discrepancies in the religious symbols―like the inversion of the arch-positions of the angel and the Virgin, the incomplete, broken bodies―and the silent withdrawal of forms, convey an allusive presence of the spiritual. Yet the functions of the medieval cult objects have evolved into dissimilar patterns, transformed by the modern gaze into mere aesthetic objects of contemplation in a museum. The modern viewer’s projected look, stepping through the doors of the Rome church rich in images, might well restore the exchange which lies at the heart of religious devotion.